PENYULUHAN MENU SEIMBANG DAN MANFAAT TABLET BESI SEBAGAI UPAYA MENCEGAH KEJADIAN ANEMIA PADA REMAJA PUTRI SMA DI KECAMATAN SUKAWATI KABUPATEN GIANYAR - Komang Agusjaya Mataram (Jurnal Pengabmas Masyarakat Sehat, 2020)
The aim of community service is that high school youth after attending counseling can increase knowledge about balanced menus and the benefits of iron tablets in an effort to prevent anemia. Increasing the value of pre-test-post-test the level of knowledge about the balanced menu and the benefits of target iron tablets (blood-added tablets) at SMKN 1 Sukawati ranged from 0.0-50.0 with an average of 16.5 (SD = 11.39), whereas in SMAN 1 Sukawati ranged from 0.0-58.3 with an average of 32.1 (SD = 16.51). Based on a paired test statistical analysis it turns out that the pre-test value of the level of knowledge is significantly different compared to the value of the post-test (p = 0,000), which means the counseling method provided is effective for increasing target knowledge about balanced menus and the benefits of iron tablets. In practice the balanced menu is generally good because it meets the principle of a balanced menu. The menu type is good, namely consumption for lunch consisting of staple foods, animal and vegetable side dishes, vegetables and fruit. The number of menus selected still needs attention, especially the amount of vegetables and rice.